Multimedia-Based Computer Network Media Applications - Syuryadi, Syuryadi; Asbara, Nurkhalik Wahdanial; Nurani, Nurani (Universitas Islam Kuantan Singingi, 2021)
This application aims to understand computer networks easily by using multimedia applications to unite motion, images, text, and sound with the result that visible more visually and more alive. With this method, it is hoped that students will quicly understand computer network science. The results of the research show that it has been designed and tested on students where this application has an evaluation within and listening to the material as guide, it is hoped that this application can make students easy to learn computer networks.